Keragaan Agronomi dan Hasil Biji Kacang Hijau pada Lima Dosis Pupuk NPKS di Lahan Sawah: Keragaan Agronomi dan Hasil Biji Kacang Hijau pada Lima Dosis Pupuk NPKS di Lahan Sawah - Sutrisno Sutrisno; Muhammad Halimi; Henny Kuntyastuti (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Mungbean is one of the main commodity which are planted in the dry season after planting rice. Even though having a high marketable value, the productivity of mungbean is still quite low because the farmers rarely provide enough fertilizer dosage and use the low growed seeds which resulted directly to the low quality or productivity. This study aims to determine the response of three mungbean varieties in paddy fields with five levels of NPKS (15:15:15:10) fertilizers. The study was consisted of three varieties (Vima-1, 2, 4) and five doses of NPKS fertilizer (100, 200, 300, 400, 500 kg ha-1). The study was applied to the randomized completely block design with three replications. The results showed that plant height, number of clusters, biomass dry weight, and seed yield ha-1 of mungbean are significant different between Vima-1, Vima-2 and Vima-4 varieties, while the addition of NPKS inorganic fertilizers could increase plant height and root weight. The interactions between varieties and the NPKS fertilizer dosage was experienced in the number of pods and seed weight per plant. The highest yield of mungbean was resulted in Vima-1 (2.18 tons ha-1) whereas the lowest yield was obtained by Vima-2 which resulted in seed 1.42 tons ha-1. The application of inorganic fertilizer NPKS (15:15:15:10) 100 kg ha-1 has quite enough to produce an optimum productivity of mungbean in Malang rice fields.